Effects of mixture powder of black rice (Oryza sativa L indica), red beans (Phaseolus vulgaris L), and moringa leaves (Moringa oleifera L) on blood glucose concentration in hyperglycemic Rats - Lalu Juntra Utama; Suryana Suryana; Anita Christina Sembiring (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Diabetes mellitus, increased blood glucose or hyperglycemia, is associated with increased oxidative stress and cardiovascular diseases. This condition will further cause carbohydrate and fat metabolism change, resulting in the decreased antioxidant defense system. Black rice, red beans, and moringa leaves contain oleic acid, butyric amino acid, antioxidants, phytic acid, and arginine, which can improve insulin sensitivity, and blood glucose homeostasis.Objective: This study aimed to analyze the effect of betamelor (black rice, red beans, and moringa leaves) on blood glucose in ratsMaterials and Methods: The design of this research was experimental research with pre-and post-control group design. A total of 20 Sprague Dawley female rats were divided into four groups, namely standard feed (PS), 80% feed of betamelor (PB8), 50% feed of betamelor (PB5), and 20% feed of betamelor (PB2). Betamelor intervention was given as much as 5% of weight for 28 days. Fasting Blood Glucose (FBG) levels were measured using the GOD-PAP method. Blood glucose data were analyzed by Analysis of Variance (ANOVA) at a 95% confidence level and using Duncan's test.Results: There were differences in FBG between groups after the intervention of betamelor. The results showed that after 28 days of intervention, betamelor decreased the serum glucose concentration from 122.69 mg / dL to 97.70 mg / dL (20.37%) in the PB8 group and from 123.91 mg / dL to 113.28 mg / dL (8.58%) in the PB5 group, but the standard diet (PS) increased by 5.73%. This result can be applied to reduce blood glucose levels in obese and patients with metabolic syndrome.Conclusions: There was a significant effect of giving a mixture of black rice, red beans, and Moringa leaves on fasting blood sugar in rats.